Myricitrin Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury: Involvement of Heat Shock Protein 90 - Wang, Min; Sun, Gui-bo; Du, Yu-yang; Tian, Yu; Liao, Ping; Liu, Xue-song; Ye, Jing-xue; Sun, Xiao-bo (Frontiers in Pharmacology, 2017)
Modulation of oxidative stress is therapeutically effective in ischemia/reperfusion (I/R) injury. Myricitrin, a naturally occurring phenolic compound, is a potent antioxidant. However, little is known about its effect on I/R injury to cardiac myocytes. The present study was performed to investigate the potential protective effect of myricitrin against hypoxia/reoxygenation (H/R)-induced H9c2 cardiomyocyte injury and its underlying mechanisms. Myricitrin pretreatment improved cardiomyocyte viability, inhibited ROS generation, maintained the mitochondrial membrane potential, reduced apoptotic cardiomyocytes, decreased the caspase-3 activity, upregulated antiapoptotic proteins and downregulated proapoptotic proteins during H/R injury. Moreover, the potential targets of myricitrin was predicted using Discovery Studio software, and heat shock protein (Hsp) 90 was identified as the main disease-related target. Further mechanistic investigation revealed that 17-AAG, a pharmacologic inhibitor of Hsp90, significantly blocked the myricitrin-induced cardioprotective effect demonstrated by increased apoptosis and ROS genera¬tion. These results suggested that myricitrin provides protection to H9c2 cardiomyocytes against H/R-induced oxidative stress and apoptosis, most likely via increased expression of Hsp90.